Cennostnye orientacii junych sportsmenov-legkoatletov na zdorov'esberezenie v processe sportivnoj podgotovki - Gorochov, N. M. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2005)
During the sports perfection the valuable orientations of track&field athletes undergo the essential changes. At the initial stage of sports specialization they are clearly defined by the expressed needs for the achievement of the sports success, gradually growing ripe, actualized during the purposeful educational influences of a coach by the needs in the healthsaving.